PENINGKATAN HASIL BELAJAR MATEMATIKA MELALUI PENDEKATAN KONTEKSTUAL DI KELAS V SEKOLAH DASAR - Suratun (ABDAU : Jurnal Pendidikan Madrasah Ibtidaiyah, 2019)
The purpose of this research is to improve mathematics learning outcomes through a contextual approach in fifth grade of elementary school. This type of research is a class action research of 2 cycles. Each cycle consists of 4 stages, namely planning, implementation of action, observation and reflection. The research subjects were fifth grade elementary school students. Data collection techniques using observation, interviews, documentation and tests. There is an increase in student learning outcomes as indicated by an increase in learning outcomes in each cycle. Student learning outcomes can be seen from the student learning completeness in cycle I with an average score of 71.2 and 60% mastery, then in cycle II it increases with an average value of 85.6 and learning completeness 90%.